2004
DOI: 10.1590/s1677-55382004000100004
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of lymphocele incidence following 450 renal transplantations

Abstract: Objective: To determine the incidence of lymphocele in the follow-up of patients who underwent renal transplantation, as well as potential factors responsible or associated to its development.Materials and Methods: All records from patients who were treated for lymphocele in our institution between May 1989 and December 2002 were reviewed, as well as their clinical outcome following treatment.Results: Among 450 patients who underwent renal transplantation in the period, only 3 required treatment, with 2 of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 9 publications
0
19
1
1
Order By: Relevance
“…Significant association was found in the adult literature between lymphocele formation and diabetes, tacrolimus therapy, and acute rejection, but we could not confirm this in our pediatric cohort . Recent papers have demonstrated that recurrent acute rejection episodes are associated with the formation of lymphocele in adults .…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…Significant association was found in the adult literature between lymphocele formation and diabetes, tacrolimus therapy, and acute rejection, but we could not confirm this in our pediatric cohort . Recent papers have demonstrated that recurrent acute rejection episodes are associated with the formation of lymphocele in adults .…”
Section: Discussioncontrasting
confidence: 83%
“…It is known that the primary cause of lymphocele is the inadequate ligation of afferent lymphatic vessels accompanying the recipient iliac vessels and the micro‐ or macrodecapsulations of the graft . It is a common surgical belief that to reduce the risk of lymphocele formation, the dissection of the recipient main vessels should be restricted to the least possible, and the lymphatic vessels present at the hilum of the kidney allograft be ligated precisely . In our institution, we have always peformed an accurate ligation of the donor and recipient lymphatic channels based on the fact that lymph does not have any clotting factor and so it is unable to seal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 Meticulous dissection of the iliac vessels with clipping of all visible lymphatics decreases the risk of lymphocele formation. 35 Treatment of lymphoceles includes percutaneous drainage and injection of sclerosing agents by skilled interventional radiologists or surgical creation of a peritoneal window in those that are not easily accessible percutaneously. 36,37 Urine leak occurs in approximately 1% to 3.5% of kidney transplant recipients.…”
Section: Urologic Complications and Postoperative Considerations In Tmentioning
confidence: 99%
“…By contrast lymphocoele is a well known complication in renal transplant surgery with incidences ranging from 0.6 to 18% [4,12,14]. This high incidence could be linked to dissection along the iliac vessels, the use of immunosuppressive medication interfering with soft tissue healing as well as with acute graft rejection, decapsulation or urinary obstruction [3].…”
Section: Discussionmentioning
confidence: 99%